IT Valuation Deployer Information System Implementation at PT Telkom Indonesia Access B3E Approach: IT Valuation Deployer Information System Implementation at PT Telkom Indonesia Access B3E Approach - Muhammad Aliy Zulfanny; Wahyu Rudianto (Jurnal Mantik, 2020)
Telkom Akses is a subsidiary of Telkom which is a state-owned company in Indonesia. Telkom Akses is engaged in telecommunications, especially the construction of Optical Fiber, Construction to Design Data and Inventory activities. In carrying out optical fiber development, Telkom Access has an information system called Deployer. Deployer's information system documents all activities from surveying, construction to inventory. This involves all parts of Telkom access, especially in the construction division. To get valid information about this information system, it is effective and efficient for the company as well as the feasibility of developing it. So, this study was conducted entitled "IT Valuation Implementation of Information Deployer Systems at Pt Telkom Akses Indonesia with the B3E Approach". This research was conducted with the B3E method with the aim of getting output in accordance with expectations including the effectiveness and efficiency of this information system, feasible to be updated or not, facilitate Telkom access in monitoring a project or not. After doing research on this information system, the data we get from the results of the questionnaire states that this information system is very helpful for Telkom Access in reporting and monitoring a project. It can also be concluded that this information system is effective and efficient for Telkom Access and deserves to be developed and updated.